Effects of unilateral resistance training on sexagenarians : an examination of functional, histochemical, biochemical, and morphological changes - O'Neill, David Edward Thomas (My University, 1997)
The purpose o f this study was to investigate functional, histochemical, biochemical and morphological properties associated with resistance training in the elderly. Ten (8 females, 2 males), moderately active sexagenarians (mean age = 66.3; S.D. +/- 3.7 yrs), volunteered to engage in 8 weeks of isotonic resistance training of the quadriceps muscle of one leg. Training sessions took place three times per week with each session including a warm up and warm down; and three to five sets (ten repetitions per set) of unilateral leg extensions and unilateral leg curls. There were no significant changes in height, weight, and thigh girth with training. Peak torque output at 180 deg/s increased 30.8% (P < 0.05) after training in the experimental limb. No significant changes in peak torque (Pre 78.1 +/- 10.5 N. m; Post 89.1 +/- 15.2 N. m) or mean power (Pre 91.6 +/- 14.5 Nmrads x s-1 Post 106.4 +/- 18.7 Nmrads x s-1) at 60 deg/s were observed. No significant change in peak torque or mean power was noted in the contralateral control limb at either velocity. Although there was a tendency to an increased fibre area in type II fibres (7.3% for IIa and 10.6% for Ilb), fibre cross sectional area (CSA) was unaltered as a result of the resistance training. In addition, there were no significant changes in the muscle fibre type composition, as assessed histochemically or in the proportion o f type I myosin heavy chain (MHC) and heat shock protein 72 as assessed by western blot. These data suggest that an eight week resistance training program is capable o f producing significant increases in isokinetic peak torque in the elderly.
Keywords: Isometric exercise Physiological aspects; Exercise for the aged Physiological aspects